Session Chair - Christofi, Michael (My University, 2026)
The purpose of the PDW was to introduce the systematic literature review methodology to both junior and senior scholars and provide them with developmental feedback on their current systematic literature review papers in International Marketing research. While we hope that many of these papers will eventually be submitted to IMR Special Issue, the purpose of the PDW is broader: to improve the quality of systematic literature review papers in International Marketing research and to bring new scholars successfully into the International Marketing field.